Changes in Lung Ultrasound in Systemic Sclerosis Before and After Rehabilitation: A Comparative Study Between People with and Without Interstitial Lung Disease - Samantha Gomes de Alegria; Matheus Mello da Silva; Jéssica Gabriela Messias Oliveira; Beatriz Luiza Pinheiro Alves de Azevedo; Nathália Alves de Oliveira Saraiva; Isabelle da Nóbrega Ferreira; Joana Acar Silva; Thiago Thomaz Mafort; Cláudia Henrique da Costa; Agnaldo José Lopes (Advances in Respiratory Medicine, 2025)
There is limited research on the impact of a physiotherapy-guided rehabilitation program (PGRP) on lung structure in systemic sclerosis (SSc). Lung ultrasound (LUS) has been used for over a decade to identify interstitial lung disease associated with SSc (SSc-ILD). This study aims to evaluate the impact of a PGRP on LUS signals in women with SSc-ILD and women without ILD (SSc-wILD). This is a longitudinal quasi-experimental study that included 33 women with SSc. The results show that changes in LUS were observed in 22 participants, especially B-lines > two. Before the PGRP the median of B-lines > two was three (0–7), while after the PGRP it was three (0–6) (p = 0.020). The aeration score was eight (0–16.5) pre-PGRP and three (0–16) post-PGRP (p = 0.013). Analyzing the impact of the PGRP on LUS signals in SSc-ILD and SSc-wILD groups, the main change observed was a reduction in B-lines > two between pre-PGRP and post-PGRP in the SSc-ILD group (p = 0.0004). The SSc-ILD group had a higher aeration score than the SSc-wILD group both pre-PGRP (p < 0.0001) and post-PGRP (p = 0.0001)]. In conclusion, LUS may be a complementary tool for assessing pre- and post-PGRP changes in people with SSc-ILD and SSc-wILD. Our data also suggest that the PGRP can elicit measurable changes in LUS findings in SSc, particularly in SSc-ILD. These findings support the inclusion of LUS in the routine monitoring of SSc and the use of a PGRP as a non-pharmacologic adjunctive strategy in SSc.